A Comparison Between the Adductor Pollicis Muscle Using TOF-Watch SX and the Abductor Digiti Minimi Muscle Using TetraGraph in Rocuronium-Induced Neuromuscular Block: A Prospective Observational Study. (21st January 2022) - Iwasaki, Hajime; Yamamoto, Mai; Sato, Hanae; Doshu-Kajiura, Akira; Kitajima, Osamu; Takagi, Shunichi; Luthe, Sarah Kyuragi; Suzuki, Takahiro
Abstract : BACKGROUND: The commonly used acceleromyography (AMG)-based neuromuscular monitor TOF-Watch SX is no longer manufactured. Recently, a new portable electromyography (EMG)-based neuromuscular monitor TetraGraph was introduced in clinical anesthesia. The aim of the study was to compare the responses obtained simultaneously from the abductor digiti minimi (ADM) muscle with TetraGraph and the adductor pollicis (AP) muscle with TOF-Watch SX during rocuronium-induced neuromuscular block. METHODS: Patients undergoing orthopedic surgery with general anesthesia were enrolled in this prospective, observational study. During total intravenous general anesthesia, train-of-four (TOF) responses following 0.9-mg·kg −1 rocuronium administration were monitored at the AP muscle with TOF-Watch SX and the ADM muscle with TetraGraph on the opposite arms. Sugammadex 2 mg·kg −1 was administered when both devices showed TOF counts (TOFCs) = 2. The primary outcome was time from rocuronium administration to first appearance of posttetanic count (PTC) response (first PTC). The secondary outcomes were baseline TOF ratios (TOFRs), onset time, time to first reappearance of TOFC = 1 (time to TOFC1), time to first reappearance of TOFC = 2 (time to TOFC2), and time from sugammadex administration to TOFR ≥0.9 with TetraGraph or to normalized TOFR ≥0.9 with TOF-Watch SX (recovery time). We used paired t test and Wilcoxon signed-rank test to analyze parametric and nonparametric data, respectively. P <.05 defined statistical significance. RESULTS: A total of 20 patients were analyzed. The baseline TOFRs were significantly higher with TOF-Watch SX than with TetraGraph (105 [96–110] vs 100 [98–101]; P = .0002). The time to first PTC (minutes) (31.7 ± 9.6 vs 41.1 ± 12.3; P < .001), time to TOFC1 (minutes) (48.0 ± 12.7 vs 58.8 ± 19.2; P < .001), time to TOFC2 (minutes) (56.2 ± 15.7 vs 74.2 ± 23.7; P < .001), and recovery time (seconds) (61.5 [32–148] vs 75.5 [94–102]); P = .043) were significantly faster with TOF-Watch SX than with TetraGraph. There were no significant differences in onset time. CONCLUSIONS: TOF-Watch SX overestimated recovery from rocuronium-induced neuromuscular block compared with TetraGraph.